EIN KANTORENBUCH AUS POMMERN - Ameln, Konrad (Jahrbuch für Liturgik und Hymnologie, 1962)
The examination of a hitherto unknown liturgical manuscript led to the following results: a) Both the external condition and the contents of the manuscript make it quite clear that it originated in Pomerania. b) It is a Cantor's Book, intended for practical use in public worship, and it contains principally those settings of the Credo, Kyrie and other parts of the Ordinarium missae and de tempore hymns for the winter section of the church year which are not contained in the Pomeranian office book. c) They include some remarkable pieces, partly with versions of the text of which there is no trace elsewhere; some others evidently come from Central Germany (Halle on the Saale, Wittenberg, Zwickau). d) The contents of the manuscript come from the 16th. century; it could have been written somewhere about 1590. In view, however, of the fact that it did not get its binding until about 1625 at the earliest, this early date of origin is unlikely. The period between 1610 and 1625 is more probable. e) Since only High German items have been included in the manuscript alongside the Latin, the author (and writer?) was probably one of the cantors from Central Germany who were working in Pomerania at that period. f) The most likely among those whose dates are known is Johann Stecher from Harten-stein in the Meissen area, who was Cantor at St. Mary's church in Köslin from 1612—1646.